Some Differential Inequalities on Time Scales and Their Applications to Feedback Control Systems - Yonghong Fan; Yangyang Yu; Linlin Wang (Discrete Dynamics in Nature and Society)
This paper deals with feedback control systems on time scales. Firstly, we generalize the semicycle concept to time scales and then establish some differential inequalities on time scales. Secondly, as applications of these inequalities, we study the uniform ultimate boundedness of solutions of these systems. We give a new method to investigate the permanence of ecosystem on time scales. And some known results have been generalized. Finally, an example is given to support the result.